The correlation between salivary acidity and dental caries on pupils at 3rd and 4th: Studi observasional - Salsabila, Dini Amalia; Tarina, Yolanda; Nababan, Hizkia Desmon Ananda; Merdekawati, Mega; Setiawan, Ignatius; Rahmawati, Dicha Yuliadewi (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRAKIntroduction: Dental caries is one of the most common dental and oral health problems in society. The degree of acidity (pH) of saliva plays an important role in the process of dental caries formation, where the more acidic the pH of saliva, the easier it is for caries to occur. A decrease in salivary pH can cause demineralization on the tooth surface, while an increase in salivary pH can encourage the growth of bacterial colonies that contribute to calculus formation. This study aims to analyze the relationship between the degree of salivary acidity and dental caries in children. Methods: This study is an analytical observational study with a cross-sectional design. The sampling method is total sampling with sample inclusion criteria coming from students in grades III and IV. Dental caries examination was carried out using the DMF-T and def-t indices, while salivary pH examination used the spitting method. The examination data were analyzed univariately to describe the characteristics of each variable, and bivariately using the Chi-square test to determine the relationship between the two variables. Results: Research shows a significant relationship between the acidity level of saliva and the level of dental caries in children. Univariately, the average salivary pH is This is proven by the p-value of 0.018 (<0.05), which is 0.018, so H0 is rejected and H1 is accepted. It was found that the more acidic the salivary pH, the higher the level of dental caries experienced by children. Conclusion: This study concludes that there is a significant relationship between the degree of acidity of salivary pH and the incidence of dental caries in students of grades III and IV of SDN 1 Mekarharja, Banjar City. This relationship is proven through statistical tests which show a p value <0.05.KEY WORDS: salivary acidity degree, salivary pH, dental karies, elementary school children, enamel demineralizationHubungan derajat keasaman saliva dengan karies gigi pada anak kelas III dan IV: Studi observasionalABSTRACTPendahuluan: Karies gigi merupakan salah satu permasalahan kesehatan gigi dan mulut yang paling umum terjadi di masyarakat. Derajat keasaman (pH) saliva memiliki peran penting dalam proses terbentuknya karies gigi, di mana semakin asam pH saliva maka semakin mudah karies terjadi. Penurunan pH saliva dapat menyebabkan demineralisasi pada permukaan gigi, sedangkan peningkatan pH saliva dapat mendorong pertumbuhan koloni bakteri yang berkontribusi terhadap pembentukan kalkulus. Penelitian ini bertujuan untuk menganalisis hubungan antara derajat keasaman saliva dengan karies gigi pada anak. Metode: Penelitian ini merupakan penelitian observasional analitik dengan desain cross-sectional. Metode pengambilan sampel yaitu total sampling dengan kriteria inkulsi sampel berasal dari siswa kelas III dan IV. Pemeriksaan karies gigi dilakukan menggunakan indeks DMF-T dan def-t, sedangkan pemeriksaan pH saliva menggunakan metode spitting. Data hasil pemeriksaan dianalisis secara univariat untuk menggambarkan karakteristik masing-masing variabel, dan secara bivariat menggunakan uji Chi-square untuk mengetahui hubungan antara kedua variabel. Hasil: Penelitian menunjukkan adanya hubungan yang signifikan antara derajat keasaman saliva dan tingkat karies gigi pada anak. Secara univariat, rerata pH saliva adalah Hal ini dibuktikan oleh nilai p-value sebesar 0,018 (<0,05), yaitu 0,018 maka H0 ditolak dan H1 diterima. Ditemukan bahwa semakin asam pH saliva, semakin tinggi tingkat karies gigi yang dialami anak. Simpulan: Penelitian ini menyimpulkan bahwa terdapat hubungan yang signifikan antara derajat keasaman pH saliva dan kejadian karies gigi pada siswa kelas III dan IV SDN 1 Mekarharja Kota Banjar. Hubungan tersebut dibuktikan melalui uji statistik yang menunjukkan nilai p < 0,05.KATA KUNCI: derajat keasaman saliva, pH saliva, karies gigi, anak sekolah dasar, demineralisasi enamel